Drop foot Post Mitral Valve Replacement and Total correction of Tetralogy of Fallot: A Two Case Report - Dewi Poerwandari; Daisy F Lapasi; Bayu Aji M (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: Peripheral nerve lesion after heart surgery was reported on brachial plexus, phrenic nerve, laryngeal recurrent nerve facial nerve, lumbosacral root and spinal cord. Incidence of peroneal communis nerve lesion after heart surgery was not much reported (0,19%). Diagnostic procedure of peripheral nerve lesion are including clinical sign and symptom,  electrophysiology studies and MRI. Rehabilitation management of peripheral nerve lesion are not only management of pain and nerve stimulation, but also walking aid beside cardiac rehabilitation due to cardiac problem.Methods: Reporting two case of peripheral nerve lesion after heart surgery. First case is a female, 37 years old suffered from drop foot two days after mitral valve replacement with mechanic valve. She got pain management, electrical nerve stimulation and therapeutic exercise beside cardiac rehabilitation program. Second case is a female, 9 years old, after total correction of Tetralogy of Fallot, got drop foot at day two. She also got pain management, electrical nerve stimulation and therapeutic exercise beside cardiac rehabilitation.Results: First case result was the drop foot getting better after she entered phase two of cardiac rehabilitation. In the second case, the drop foot was relieved at phase two cardiac rehabilitation and back to normal condition after one year after surgery.Conclusion: In these two case of drop foot after heart surgery, the drop foot was relieved after pain and rehabilitation management beside cardiac rehabilitation.